Sustainable Tourism Planning During the COVID-19 Pandemic: A Semi-Systematic Literature Review and Bibliometric Analysis - Rian Destiningsih; Yunastiti Purwaningsih; Tri Mulyaningsih; Akhmad Daerobi (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The purpose of this study is to synthesize research results on the topic of sustainable tourism planning during the COVID-19 pandemic using the Scopus database. Method: A semi-systematic literature review (SSLR) with identification, screening, eligibility and inclusion on bibliometric analysis. Results: Research shows that the topic of sustainable tourism planning during the COVID-19 pandemic still offers extensive research opportunities; the pandemic has had both positive and negative impacts on tourism sustainability; and that tourism sector recovery requires multi-stakeholder collaboration involving communities, government, the private sector, academics, and tourists, taking into account environmental, economic, and socio-cultural aspects. The findings of this study indicate that publications on sustainable tourism planning during the COVID-19 pandemic still offer opportunities for deeper exploration in this context. Novelty: This study provides a comprehensive synthesis of trends and directions for the development of sustainable tourism planning during the COVID-19 pandemic, while emphasizing the importance of a multi-stakeholder collaborative approach as the basis for the recovery and sustainability of the tourism sector post-pandemic.